Pengaruh Tingkat Perputaran Kas, Pertumbuhan Kredit dan Rasio BOPO pada Profitabilitas LPD di Kota Denpasar Periode 2006-2010 - Bayu Prawira, I Wayan Adi; Wisadha, I Gede Suparta (E-Jurnal Akuntansi, 2012)
The LPD is have rule to support rural economies it can not be separated from its ability in get the profit. The ability of LPD to generate earnings can not be separated from the its ability to manage their assets and debts. The profitability an LPD can be affected by several factors such as: cash turnover, credit growth, and ROA ratios. This study aims to find out the effect of cash turnover, credit growth, and ROA ratios simultaneously and partially towards LPD’s profitability in Denpasar period of 2006-2010. The data analysis technique were used multiple linear regression analysis techniques. The conclusions of this research were partially and simultaneously cash turnover, credit growth, and ROA ratios have significant impact towards the LPD’s profitability in Denpasar period of 2006-2010. Keywords: Turnover Rate Cash, Credit Growth, ROA ratio, Profitability